The Effect of Operating Cash Flow on Earnings Quality: The Moderating Role of Leverage in Indonesian Industrial Sector Firms - Sulton Afzani; Eni Srihastuti; Agus Athori (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the direct effect of operating cash flow on earnings quality and evaluates the moderating role of leverage in industrial sector companies listed on the Indonesia Stock Exchange during the post-pandemic recovery period of 2022-2025. Employing a quantitative explanatory design, secondary data were gathered from audited annual financial statements of 41 firms selected through purposive sampling, yielding 164 firm-year observations. Earnings quality was measured as an inverse proxy via the absolute value of discretionary accruals (ABSDA) using the Modified Jones Model. Due to significant heteroskedasticity violations in the diagnostic phase, the model was estimated using Robust Standard Errors with the HC3 estimator. The empirical results demonstrate that operating cash flow does not significantly affect earnings quality. This indicates that operational cash metrics during this transitional timeline were driven by defensive liquidity survival rather than financial report modification. Furthermore, leverage fails to moderate the relationship, as stringent debt covenants independently restrict interactive accrual manipulation. Conversely, firm size exhibits a significant negative effect on ABSDA, confirming that a larger corporate scale is associated with superior earnings quality due to heightened public scrutiny and robust internal controls. These findings suggest that capital market participants should prioritize corporate scale over isolated cash metrics when assessing financial reporting integrity.